PEMULIHAN GIZI BURUK SECARA RAWAT JALAN DI PUSKESMAS - S. Suwarti; Amelia Amelia; S. Muljati; E. Rustan; Reviana Reviana; Heryudarini Harahap; Sihadi Sihadi (Persagi, 2003)
OUT-PATIENT MANAGEMENT FOR SEVERE MALNOURISHED CHILDREN IN PUSKESMASBackground: During economic crisis in Indonesia in mid 1997, the numbers of malnourished children has increased. Many efforts had been conducted to solve this problem to prevent the detrimental effect of malnutrition especially in the reduction of the quality of manpower. Since 1980's our ambulatory clinic has developed the management for malnourished children. From 1997 to 2000, cases of malnourished children increased from 27 to 193, but we were facing with the numbers of defaulters. There were 40-50% drops out patients. To solved this problem, we worked together with Districts Health Office (Dinas Kesehatan Kabupaten and Kota) Bogor to build nutrition clinic in 3 health centers (Puskesmas), in South Bogor, Sukaraja, and Sukamanah sub district. Objectives: To build the nutrition clinic in health center. Methods: First step of our action was to train the medical doctors, nurses and nutritionist from the health centers in ambulatory management (registration, anthropometric measurement, nutrition counseling, clinical examination and medication for infectious diseases) of severe malnourished children. The second step was to arrange the nutrition clinic in the health centers. In the first three months, the clinic was run by the team of the Nutrition Research and Development Center together with the team of health centers. In the second three of months, the health centers team run the clinic and NRDC team only supervised them. Results: The activity of nutrition clinic in the health centers was no difference with the activity in the nutrition clinic in the NRDC. The children nutritional status was improved after 4 months intervention. The improvement was measured by weight-for-height as well as by weight-for-age. The weight-for-height index was found as the perfect indicator to measure the effect of intervention on the nutritional status of the children. Conclusions: Community health centers staffs has a potential capacity to solve malnutrition problem, especially when they were trained adequately by proper trainer, and the best parameter to evaluate nutritional status was weight-for-height. Keywords: out-patient, severe malnutrition